Secrets of the digital detectives. (Economist, 2006)
This article reports on the software being used to detect fraud. One of the highlighted markets, for car insurance, allows computers to compute variables that would otherwise be undetectable or too complicated for a human fraud detector. For instance, most claims filed over the weekend or on a Monday are false, but the software can compute other factors, such as the owner's affluence, the injury to the driver and the resale value of the car can also be used to determine the claim's validity. This software is also applied to the online shopping businesses, airlines and telecom industry; it also blocks transactions by most third world countries.